Financial Integration and Rebalancing in Asia - Unteroberdoerster, Olaf (IMF Working Papers; Working Paper, 2011)
The paper shows that Asia's degree of financial integration, both with the world and within the region remains low by various measures. The paper also provides empirical evidence that greater financial integration can support economic rebalancing in statistically meaningful ways. The implication is that in the debate on managing capital inflows the longer-term benefits of financial openness for broader-based growth should not be forgotten.